Azo-triazolide bis-cyclometalated Ir(III) complexes via cyclization of 3-cyanodiarylformazanate ligands - Mu, Ge (Dalton Trans, 2019)
In this work we describe the synthesis of sterically encumbered 1,5-diaryl-3-cyanoformazanate bis-cyclo-metalated iridium(III) complexes, two of which undergo redox-neutral cyclization during the reaction to produce carbon-bound 2-aryl-4-arylazo-2H-1,2,3-triazolide ligands. This transformation offers a method for accessing 2-aryl-4-arylazo-2H-1,2,3-triazolide ligands, a heretofore unreported class of chelating ligands. One formazanate complex and both triazolide complexes are structurally characterized by single-crystal X-ray diffraction, with infrared spectroscopy being the primary bulk technique to distinguish the formazanate and triazolide structures. All complexes are further characterized by UV-Vis absorption spectroscopy and cyclic voltammetry, with the triazolide compounds having similar frontier orbital energies to the formazanate complexes but much less visible absorption.